Teaching oscillations and waves during the COVID-19 pandemic using the flipped classroom - Sariaman Siringo Ringo; Rahmadhani Mulvia (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
The COVID-19 pandemic has posed a major challenge to education systems around the world. Schools and universities were encouraged to eliminate or limit face-to-face learning activities to prevent the spread of COVID-19. In this present study, the flipped classroom model has been proposed as a solution to this challenge. The purpose of this research was to investigate the effect of the flipped classroom model on students’ cognitive learning outcomes in learning oscillations and waves. The learning achievement was measured by the Oscillations and Wave Achievement Test (OWAT) consisting of 15 items. This pre-experimental with a one-group pretest-posttest design was conducted at a small public school in Tanjung Jabung Barat, Jambi. A total of 27 junior high school students participated in this present research. The results of average normalized gain showed that the use of the flipped classroom model had a positive effect on students' cognitive learning outcomes in learning oscillations and waves.